(untitled) (Research, Society and Development, 2021)
Objectives: understand the daily lives of nursing managers regarding violence in the work environment; relate managerial strategies with disruptive behaviors in the nursing team. Method: this is a descriptive-exploratory research with a qualitative approach. Five managers from the Nursing area were interviewed by means of recorded interviews with guiding questions. Results: from the speeches, three categories emerged: "Articulate actions in the face of power relations"; "Dialog and welcome when faced with adverse situations"; "Importance of support from top management". Conclusion: the analysis of the speeches allowed us to understand the experience of nursing managers in their different work environments in relation to situations that involve risks to workers’ health and the quality and safety of the care provided.